Evaluation of the Hepatotoxic Effect of MSP on the Histomorphology of Pregnant Wistar Rats - Francis Ojochogwu Omale (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: The search for safe, affordable, and effective plant-derived fertility-regulating agents has increased considerably due to the limitations and adverse effects associated with synthetic contraceptives. Medicinal plants possessing anti-fertility and reproductive outcomes have attracted attention as potential alternatives for fertility control. Objective: This study investigated the hepatotoxic effects of a Moringa seed powder in pregnant female albino Wistar rats through evaluation of body weight difference, and histopathological examination of the organs. Methods: Adult female albino Wistar rats were assigned to control and treatment groups. Animals were mated and pregnancy was confirmed before administration of graded doses of the extract during the early gestational period. Histological evaluation of fetal heart, lungs, kidney, and liver tissues was performed using hematoxylin and eosin staining. Statistical analysis was conducted using Student’s t-test, pre-test and Post-test with significance set at p < 0.05. Results: Maternal weight profiles varied across treatment groups. The highest reduction in body weight was observed in the highest-dose treatment group (1000 mg/kg of MSP), suggesting dose dependent reproductive toxicity. Student T-test, pre-test, and post-test analysis among weight measurements on Days 7, 14, and 20, indicating unstable responses during treatment. Histological examination of control litter tissues showed normal cardiac, renal, and hepatic architecture but the pregnant rats treated with MSP showed inflammations of the hepatocytes. Conclusion: The findings suggest that Moringa oleifera seed powder caused reductions in maternal body weight and pregnancy outcome which supports its potential reproductive modulating effects. Further investigations involving hormonal assays, molecular mechanisms, and phytochemical characterization are recommended.